Exploring fecal sludge treatment technologies in humanitarian settings at Cox’s Bazar, Bangladesh: a comprehensive assessment of treatment efficiency through characterization of fecal sludge - Islam, Mohammad Rafiqul; Alam, Mohammad Atique Ul; Moniruzzaman, M.; Galib, Faisal Chowdhury; Hossain, Md. Sakib; Hussain, Mohammed Tanveer; Paul, Partha; Islam, Md. Tamzid; Uddin, Salman Zahir; Islam, Md. Shafiqul; Hossain, Md. Ferdous; Rahman, Md. Mominur; et al. (Frontiers in Environmental Science, 2024)
Introduction: Efficient treatment of fecal sludge in densely populated settings is essential as it has a direct impact on public health and the environment. This study presents a comprehensive assessment of fecal sludge treatment technologies in Rohingya camps at Cox's Bazar, Bangladesh, focusing on removal efficiencies and compliance with regulatory standards. Methods: Seventeen treatment plants of five different technologies were evaluated based on removal efficiency and standard discharge guidelines for various physicochemical and microbiological parameters. Results: Waste Stabilization Pond was the top performer compared to four other different treatment technologies evaluated, achieving notable removal rates: 97.3% reduction in E. coli, 100% in helminth eggs, 98.3% for COD, 97.8% for BOD, 98.7% for TSS, 92.1% for TS, 82.8% for phosphate, and 93.3% for total nitrogen. Lime Stabilization Ponds showed lower removal rates, except for E. coli (98.9%), with reductions of 99.7% for helminth eggs, 81.6% for COD, 80.9% for BOD, 86.3% for TSS, 68.6% for TS, and 49.2% for phosphate. Upflow Filters demonstrated good removal efficiencies for E. coli (99.7%), TSS (95.9%), COD (91.7%), BOD (93.5%), and helminth eggs (93.7%). WSP consistently outperformed other technologies across all seasons. Despite these, none of the technologies fully met discharge standards. Discussion: These findings highlight the need for a comprehensive approach, the combination of physicochemical and biological processes, to enhance efficacy. Promoting improved fecal sludge management technologies through awareness campaigns and technical support can mitigate environmental health risks in densely populated humanitarian settings.